“Decolonising” museums through experimental practices: the case of MUBIG, a neighbourhood museum in Milan - Cimoli, Anna Chiara (Annales Universitatis Paedagogicae Cracoviensis. Studia de Arte et Educatione, 2022)
The article is focused on MUBIG, an experimental museum in a peripheral neigbourhood of Milan. The museum, a fluid, scattered, dynamic discourse – a process, more than a place – is born out of an urban regeneration project. The reflection attempts to articulate a number of key questions: how are the individual histories embodied by the museum? What points of fragility are envisaged in this regard and how are they addressed, in order to prevent tokenism and the rhetoric of participation perse? What is the role of the visual dimention and of contemporary art? Throughout the article, I argue that neighbourhood museums might be one of the many actors needed on the scene of decolonisation, by this term meaning a process of space-making around the commons based on representation and radical listening. The experience is analyses here through a double lens: while being a member of the collective who co-designed it, I also look at it from my academic position. This allows me to describe the process keeping different “points of distance,” therefore layering methodologies and viewpoints.